Accessory muscle in the forearm: a clinical and embryological approach - Çıftçıoğlu, Engin (Korean Association of Anatomists, 2011)
Muscular variations of the flexor compartment of forearm are usual and can result in multiple clinical conditions limiting the functions of forearm and hand. The variations of the muscles, especially accessory muscles may simulate soft tissue tumors and can result in nerve compressions. During a routine dissection of the anterior region of the forearm and hand, an unusual muscle was observed on the left side of a 65-year-old male cadaver. The anomalous muscle belly arose from the medial epicondyle approxiamately 1 cm posterolateral to origin of normal flexor carpi ulnaris muscle (FCU), and from proximal part of the flexor digitorum superficialis muscle. It inserted to the triquetral, hamate bones and flexor retinaculum. Passive traction on the tendon of accessory muscle resulted in flexion of radiocarpal junction. The FCU which had one head, inserted to the pisiform bone hook of hamate and palmar aponeurosis. Its contiguous muscles displayed normal morphology. Knowledge of the existence of muscle anomalies as well as the location of compression is useful in determining the pathology and appropriate treatment for compressive neuropathies. In this study, a rare accessory muscle has been described.